2020
DOI: 10.21873/anticanres.14176
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Laparoscopic Surgery in Colorectal Cancer Patients With Dialysis

Abstract: Background/Aim: To investigate the outcomes of laparoscopic surgery in colorectal cancer patients with dialysis. Patients and Methods: Fourteen dialysis (dialysis group) and 567 non-dialysis (non-dialysis group) patients who underwent laparoscopic and open surgery for colorectal cancer between April 2008 and December 2015 were included. Short-term and long-term outcomes were compared between the groups. A 1:2 propensity score matching was performed to compare long-term outcomes. Results: All the dialysis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Similar to previous studies reporting that the rate of morbidity and mortality related to CRF was higher, our study showed the same result: the rate of complications of CRF patients on dialysis were higher (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In previous studies investigating laparoscopic colon surgery for dialysis patients, Higashino et al and Obara et al reported that there were no significant differences in operative outcomes and postoperative short-term outcomes between dialysis patients and other patients (20,21). In our study, the fact of that the rate of open surgery in Group A was higher may have had a strong impact on the result.…”
Section: Discussioncontrasting
confidence: 39%
“…Similar to previous studies reporting that the rate of morbidity and mortality related to CRF was higher, our study showed the same result: the rate of complications of CRF patients on dialysis were higher (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In previous studies investigating laparoscopic colon surgery for dialysis patients, Higashino et al and Obara et al reported that there were no significant differences in operative outcomes and postoperative short-term outcomes between dialysis patients and other patients (20,21). In our study, the fact of that the rate of open surgery in Group A was higher may have had a strong impact on the result.…”
Section: Discussioncontrasting
confidence: 39%
“…The NOS score and definitions of the CKD group and the non-CKD group are shown in Table 1 . Six studies reported that the modification of diet in renal disease equation was used to estimate the estimated glomerular filtration rates (eGFR)[ 16 , 18 , 25 , 27 - 29 ]; however, the method used in the other studies was unclear[ 15 , 17 , 26 ] (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these events might increase the risk of lung-related complications[ 18 ]. Cardiovascular complications might be associated with endothelial dysfunction in CKD patients[ 16 , 34 ]. Furthermore, patients with CKD are in a relatively immunosuppressive state due to nutritional deficiencies, the lymphocyte suppression and the loss of serum immune system components, which might result in an increase in infectious diseases and short-term deaths after surgery[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various conventional treatment methods have been established for CRC, including surgery, chemotherapy, and radiotherapy. Additionally, novel therapies like bio‐targeted therapy, immunotherapy, and precision therapy have been introduced 2–7 . However, the prognosis for advanced CRC patients, especially those with distant metastasis, remains dismal.…”
Section: Introductionmentioning
confidence: 99%